EFEITO DO SEXO SOBRE O PESO E RENDIMENTO DE CARCAÇA E CORTES DE FRANGOS DE CORTE COBB 500® - Cesar, Antonio Cesar; Galuci, Andréia Fróes; Gottardi, Camila Priscila; De Souza, Aurélio Ricardo; Ferreira, Thales Silva; Ferreira, Bruno Reis (ANAIS DO ENIC, 2018)
-